INTERSECTING MARGINS: SOCIO-ECONOMIC PRECARITY AND SURVIVAL STRATEGIES OF WOMEN RAGPICKERS IN CHENNAI’S DUMPYARDS - Dhanasekar M,; S. Anitha, (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article explores the living and working conditions of women ragpickers in Chennai’s biggest dumpyards, Kodungaiyur and Pallikaranai. Based on a survey of 351 women, the study finds that most live in constant economic insecurity, with what they earn each month almost fully spent on daily needs. There is little scope for savings, and many rely on loans to manage everyday expenses. Educational levels are very low, as 71.5% of the women cannot read or write. Access to welfare is closely tied to both caste and education, with many women being left out. No one reported any help from NGOs, and the absence of formal work protections further increases their vulnerability. Using ideas from intersectionality, Marxist theory, and feminist political ecology, the study shows that caste, gender, and city policies all work together to keep women ragpickers on the margins, even though their work is vital for waste management in Chennai. The article ends by recommending changes in policy, such as formal recognition of these workers, better welfare access, education programs, and city planning that pays attention to women’s needs. It argues that real improvement will need a major change in how urban work and social support are organised.